Pemberdayaan Tenaga Kesehatan Pada Program Pemanfaatan Obat Tradisional - Sri Suwarni; Atalia Ina Bulu; Metrikana Novembrina; Amalia Solichati Rizqi; Pertiwi Setyaningrum (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Traditional medicine is something that exists in society and is always a question from patients. The use of traditional medicine as a treatment effort by the community continues to increase. Purpose of improving public health through health workers by utilizing traditional medicines available in the environment. The method used in the implementation of this activity is counseling and training. Results of the Service went well and smoothly. Conclusion There is an increase in knowledge and skills after training compared to before training